Farm trial on fish-free diet with low protein content in blue foxes (Alopex lagopus) - Dahlman, Tuula; Pölönen, Ilpo; Jäykkä, Heikki; Valkosalo, Kari; Jalava, Taina (Nordiska Jordbruksforskares Förening (NJF), 2001)
v ok